Toward sustainable plastic bioremediation using bacterial consortia from aquatic environments - Alharbi, Maha; Abd-elhaliem, Safaa Mohamed; Afifi, Salwa S.; Al-shareef, walaa A.; Mosbah, Rasha A.; Mansour, Abdallah Tageldein; Alharbi, Nada K.; Bendary, Mahmoud M. (Frontiers in Bioengineering and Biotechnology, 2026)
BackgroundPlastic pollution has become a pervasive global challenge, threatening both aquatic ecosystems and human health. This study explores the biotechnological potential of native microorganisms from diverse aquatic environments for the biodegradation of synthetic plastics and microplastics.Methodology and resultsA total of 200 water samples were collected from freshwater and saltwater sources, yielding 277 bacterial isolates. Preliminary screening showed that approximately one-third of these isolates exhibited plastic-degrading activity, supported by enzymatic functions such as catalase, lipase, protease, esterase, and peroxidase. Seasonal and spatial variations shaped microbial diversity and enzymatic potential, with saltwater habitats harboring the highest diversity. Molecular identification using 16S rRNA gene sequencing revealed that the most efficient degraders were Micrococcus luteus, Enterobacter cloacae, Corynebacterium aurimucosum, and Mesobacillus maritimus. Structural and chemical analyses using scanning electron microscopy (SEM) and nuclear magnetic resonance (NMR) provided clear evidence of polymer degradation in both commercial and environmentally collected plastics, with the latter showing greater susceptibility due to pre-weathering. High-performance liquid chromatography (HPLC) further confirmed the presence of plastic-derived contaminants in aquatic samples, particularly in wastewater effluents.ConclusionA bacterial consortium composed of confirmed high-efficiency degraders demonstrated remarkable plastic-degrading capacity, highlighting its potential for application in bioremediation strategies within aquatic environments. This consortium was capable of breaking down polyethylene, polyethylene terephthalate, polyhydroxyalkanoates, and low-density polyethylene. These results emphasize the ability of indigenous microbial communities to degrade persistent plastics and underscore their promise for developing eco-friendly bioremediation strategies to mitigate aquatic plastic pollution.